Correlates of Taiwanese Gay and Bisexual Men's Family-Building Preferences: A Mediation Analysis. Issue 10 (24th August 2022) - Lau, Bobo Hi Po; Forth, Marty W.; Huang, Yu-Te
ABSTRACT: This study investigated the role of filial piety, internalized homophobia, and desire for genetic relatedness with one's child in gay and bisexual men's family-building choice. A sample of 1, 023 Taiwanese gay and bisexual men with a desire to have a child was recruited to complete an online survey that included the Contemporary Filial Piety Scale, the Chinese Internalized Homophobia Scale, and questions about desire for genetic relatedness with a child and acceptance of adoption and surrogacy. Mediation models, with desire for genetic relatedness as a mediator, were tested. The results show that those who chose surrogacy-only were older and had higher socio-economic status than those who selected adoption-only and both options. Filial piety and internalized homophobia were positively associated with the acceptance of surrogacy-only over adoption-only and both options. Desire for genetic relatedness mediated these relationships. This finding elucidates how sociocultural factors shape family-building preferences among gay and bisexual men.